2018
DOI: 10.1111/jace.15983
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and piezoelectric properties of Ba0.85Ca0.15Ti0.90Zr0.10O3 films in 200 nm thickness range

Abstract: Lead‐free piezoelectric Ba0.85Ca0.15Ti0.90Zr0.10O3 (BCZT) thin films were fabricated on Si/SiO2/TiO2/Pt (100) substrates following chemical solution deposition technique. Microstructure of the nano‐sized BCZT particles crystallized in the thin film was thoroughly characterized. Ferroelectric, dielectric and piezoelectric properties of the films were investigated in detail. The BCZT films annealed at 800°C temperature exhibited high remanent polarization of 25 ± 1 μC/cm2, energy density of 17 J/cm3, dielectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…It is evident that the amplitude-voltage butterfly loops of the heterostructures show varying degrees of asymmetry behavior, which is also reported in previous works. , This behavior can be ascribed to the built-in electric field caused by the electrode self-poling effect, which promotes downward polarization switching and in turn hinders upward polarization rotation . Furthermore, the effective piezoelectric coefficient d 33 of the epitaxial heterostructures is determined from formula: d 33 = ( D – D 1 )/( V – V 1 ), where D is the measured value of piezoelectric displacement, V is the corresponding applied voltage at each point of the amplitude-voltage loops, D 1 is the piezoelectric displacement, and V 1 is the applied voltage of the intersection. The d 33 values of all samples calculated from the amplitude-voltage loops are recorded in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that the amplitude-voltage butterfly loops of the heterostructures show varying degrees of asymmetry behavior, which is also reported in previous works. , This behavior can be ascribed to the built-in electric field caused by the electrode self-poling effect, which promotes downward polarization switching and in turn hinders upward polarization rotation . Furthermore, the effective piezoelectric coefficient d 33 of the epitaxial heterostructures is determined from formula: d 33 = ( D – D 1 )/( V – V 1 ), where D is the measured value of piezoelectric displacement, V is the corresponding applied voltage at each point of the amplitude-voltage loops, D 1 is the piezoelectric displacement, and V 1 is the applied voltage of the intersection. The d 33 values of all samples calculated from the amplitude-voltage loops are recorded in Table .…”
Section: Resultsmentioning
confidence: 99%
“…16,17 This behavior can be ascribed to the built-in electric field caused by the electrode self-poling effect, which promotes downward polarization switching and in turn hinders upward polarization rotation. 18 Furthermore, the effective piezoelectric coefficient d 33 of the epitaxial heterostructures is determined from formula: 19…”
Section: Resultsmentioning
confidence: 99%
“…The grain size of BCZT has a great influence on the piezoelectric response, it is generally believed that the value of d 33 increased with the increase of grain size. [17,26,27] Due to the regular arrangement of the atoms or molecules in the BCZT/SRO heterostructure epitaxially grown on (001)-STO substrates, the ferroelectric domain is easy to rotate under the electric field, which is favor of the improvement of the piezoelectric properties of the film. In addition, the piezoelectric effect is enhanced via weakening the clamping effect from the substrate to BCZT thin film by setting SRO buffer layer.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Li et al reported the giant piezoelectric properties ( d 33 = 258 pm V −1 ) of BCZT thin films prepared by MS. [ 16 ] Seelam et al reported the ferroelectric and piezoelectric properties of BCZT films with thickness of 200 nm grown on Si substrates by chemical solution deposition technique. [ 17 ] By growing it on the platinized Si substrates via PLD, K. Prabahar et al revealed the effect of deposition temperature on the microstructure, ferroelectric, and mechanical properties of lead‐free BCZT ceramic thin films with thickness of 340 nm 3 . And, Wang et al reported excellent ferroelectric properties ( P r = 22.15 μC cm −2 ) of sol–gel‐synthesized BCZT thin films with 800 nm thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional lead‐based perovskite materials, such as PbTiO 3 (PTO) and PbZr x Ti 1− x O 3 (PZT), are well known for their outstanding electrical properties, but also arouse great concerns as their excessive lead content causes significant harm to the human body and environment. Consequently, the development and utilization of lead‐free materials have been promoted . For the past few years, considerable attention has been paid to lead‐free perovskite ceramics, which can be classified into three main categories as follows: K 0.5 Na 0.5 NbO 3 (KNN), Bi 0.5 Na 0.5 TiO 3 (BNT), and BaTiO 3 (BT) .…”
Section: Introductionmentioning
confidence: 99%